An approach to configuration design synthesis of subsonic transport aircraft using artificial intelligence techniques - Pasaribu, H. M. (Cranfield University, 1991)
This thesis outlines a computer system developed to tackle the configuration design synthesis of subsonic transport aircraft. The system provides an interactive design environment which combines the reasoning process of the aircraft configuration definition and the numerical analyses that lie behind the reasoning. The system applies Artificial Intelligence (AI) techniques to the configuration analysis. This gives the system the capability to reason with the configuration choices. The system is built in modules, with each module is clearly separated to deal with a complete analysis in a specific aspect of design. The integration of the modules is done through an intelligent interface and a common database. The interface also incorporates AI techniques in deciding the sequence of execution of the modules and the processing of the input/output data for a particular module. The interface permits the sharing of information among the modules and supports modularity and flexibility of the system for future development. Since each module is independent, it can be easily modified or replaced without disturbing the balance of the system. An extensive library of application programs is included in the engineering analysis module which enable detailed analysis to be performed. The system is equipped with a simplified database management and a special purpose graphics module which is extensively used for the presentation of the output. The system has been validated and tested. It can handle both propeller driven and jet engined aircraft. An example of the case studies is presented. The improvement of the system for future development is also considered. These include the extension of the knowledge base for dealing with problems in other modules, the enhancement of the application programs in the engineering module, and a possible interface with an established Computer Aided Drafting (CAD) system.